APPLICATION OF TAX CALCULATIONS BASED ONPERMANENT EMPLOYEES ARTICLE 21PPH USING MICROSOFT VISUAL BASIC 6.0 - Bernadet Bernadet; Elly Agustina J, SKom, MMSI (Jurnal Sistem Informasi, 2005)
Permanent Employee Tax Calculation based on Article 21 is an income tax on income in the form of salaries, wages, salaries, allowances and other payments by whatever name in connection with the work, services, or activities undertaken by individual taxpayers in the country as referred to in Article 21 Law No. 17 year 2000. Tax Article 21 of the end of the month or the payment of income becomes due by the end of the month concerned.